Harms of production: theorising pornography as a form of prostitution. (January 2015) - Tyler, Meagan
Synopsis: Traditionally recognised forms of prostitution (such as brothel, street and escort prostitution) tend to be seen, in both popular culture and in law, as separate from pornography. The pornography industry is often represented as a less harmful and more glamorous part of the sex industry. These representations, coupled with academic debates that have typically focused on the consumption rather than the production of pornography, have resulted in some of the harms of pornography being obscured. It is argued here that commercial pornography should be understood as prostitution and, potentially, as a form of prostitution carrying specific and additional harms. This may offer useful ways forward for feminist analyses of the harms of pornography. Highlights: The separation of prostitution and pornography found in many legal systems, and in pop culture representations, is flawed. Pornography can be better understood as a form of prostitution. Academic literature on the harms of pornography has tended to focus on harms related to consumption rather than production. Understanding pornography as a form of prostitution allows for a more comprehensive and accurate understanding of harm.